Algorithmic Foundations of Robotics VIII Selected Contributions of the Eighth International Workshop on the Algorithmic Foundations of Robotics - Chirikjian, Gregory S.; Choset, Howie; Morales, Marco; Murphey, Todd (Springer Tracts in Advanced Robotics, 2010)
This volume is the outcome of the eighth edition of the biennial Workshop on Algorithmic Foundations of Robotics (WAFR). Edited by G.S. Chirikjian, H. Choset, M. Morales and T. Murphey, the book offers a collection of a wide range of topics in advanced robotics, including networked robots, distributed systems, manipulation, planning under uncertainty, minimalism, geometric sensing, geometric computation, stochastic planning methods, and medical applications. The contents of the forty-two contributions represent a cross-section of the current state of research from one particular aspect: algorithms, and how they are inspired by classical disciplines, such as discrete and computational geometry, differential geometry, mechanics, optimization, operations research, computer science, probability and statistics, and information theory. Validation of algorithms, design concepts, or techniques is the common thread running through this focused collection. Rich by topics and authoritative contributors, WAFR culminates with this unique reference on the current developments and new directions in the field of algorithmic foundations.